Immigrant populations, work and health—a systematic literature review - Ahonen, Emily Q; Benavides, Fernando G; Benach, Joan (Scandinavian Journal of Work, Environment & Health, 2007)
' ' OBJECTIVES ': 'This paper summarizes the information on immigrant occupational health available from recent studies, incorporating varied study designs. ' ' METHODS ': 'A systematic search was carried out in PubMed employing terms of interest to the study and related terms supplied by the same search engine. Articles were selected through the following process: (i) reading the title and abstract, in English or Spanish, for the period 1990–2005, (ii) reading of the entire text of selected articles; (iii) making a manual search of the relevant citations in the selected articles; (iv) eliminating articles without a focus on the themes of central interest (immigration, work, and health), and (v) reading and analyzing the definitive article set. No quality criteria were used in the article selection. ' ' RESULTS ': 'The location of studies was not straightforward and required careful thought about the search terms. The included 48 papers were often multifaceted and difficult to categorize. They generally came from countries historically associated with immigration and described occupational risk factors, health consequences, and the social, economic, and cultural influences on worker health. They were also based on data, surveillance, training, and preventive measures that were inadequate. ' ' CONCLUSIONS ': 'Increased migration is a reality in industrialized countries all over the world, and it has social, political, and economic consequences for migrating groups, as well as for their sending and host societies. More reliable data, targeted appropriate interventions, and enforcement of existing regulations are necessary to improve the health of immigrant workers. Furthermore, studies in sending and developing countries should be encouraged to form a more complete understanding of this complex situation.
Keywords: foreign worker; health; immigrant population; labor migrant; migrant worker; occupational disease; occupational health; occupational injury; occupational safety; occupational safety and health; review; systematic review; work